Immersive virtual reality in AECO/FM to enhance education: Systematic literature review and future directions - Tastan, Hasan; Tong, Togan (WILEY, 2023)
Immersive virtual reality (IVR) is considered as an effective and efficient instructional tool for architecture, engineering, construction, operation, and facility management (AECO/FM) education. However, it is essential to systematically evaluate them to obtain consolidated evidence on the impact of IVR applications. Thus, the aim of this article is to present the state-of-the-art on all AECO/FM use cases, including learning theories/models, all key factors, and experimental design, and to suggest future directions for IVR research. This review follows a systematic literature review methodology to analyze 79 papers between 2013 and 2022. The results show that learning theories/models are not sufficiently applied. There is consensus that IVR influences affective factors positively. It is necessary to consider task type, task complexity, virtual environment design, and ergonomics of IVR tools in terms of cognitive factors. Cognitive/affective factors associated with learning performance should be examined in depth to develop more effective learning methods. Future studies should design and conduct experimental procedures with more scientific rigor.
Keywords: AECO/FM; education; immersive virtual reality; systematic literature review; training; CONSTRUCTION SECTOR; PRIOR KNOWLEDGE; DESIGN; ENVIRONMENT; TECHNOLOGIES; ARCHITECTURE; PERCEPTION; FEATURES; IMPACT; SAFETY; Computer Science; Education & Educational Research; Engineering